Partial second toe pulp free flaps in early childhood - Hong, Min Ki; Lee, Dong Chul; Choi, Min Suk; Koh, Sung Hoon; Kim, Jin Soo; Roh, Si Young; Lee, Kyung Jin (Archives of Plastic Surgery, 2020)
Background The introduction of the partial second toe pulp free flap has enabled superior aesthetic and functional results for fingertip reconstruction in adults. Children undergoing fingertip amputation for various reasons have limited options for reconstruction. Conventional treatment could shorten the finger, leading to poor cosmesis and function. We report 18 years of our experiences with fingertip reconstruction using partial second toe pulp free flaps in patients in early childhood.Methods Medical charts of children who had undergone fingertip reconstruction using partial second toe pulp free flaps from 2001 to 2018 were retrospectively reviewed. The surgical procedures were identical to those for adults, except for the usage of 11-0 nylon sutures. Patients’ demographic data, vessel size, flap dimensions, length of the distal phalanx, and functional outcomes over the course of long-term follow-up were documented. The statistical analysis was performed with the Student t-test, the Mann-Whitney U test, and Pearson correlation analysis.Results Eighteen toe pulp flaps in 17 patients (mean age, 3.0 years) were identified. All the flaps survived without any major complications. In long-term follow-up, the flap-covered distal phalanges showed growth in line with regular development. There was no donor-site morbidity, and all children adapted to daily life without any problems. In two-point discrimination tests, the fingertip sensation recovered to almost the same level as that in the contralateral finger.Conclusions Partial second toe pulp free flaps are an excellent option for fingertip reconstruction in young children, as well as in adults.
Keywords: Free tissue transfer flaps; Childhood; Fingertip; Reconstructive surgical procedure